The evaluation of the swing and aerial motion of Kovacs on horizontal bar - Lim, K.-C. (Korean Journal of Sport Biomechanics, 2020)
Objective: The aim of this study was to investigate the swing and aerial motion of Kovacs, and evaluate the skill level of Kovacs by Korean adult players on horizontal bar. Method: The subjects for this study were 6 male top athletes participated in the 46th National Gymnastics against Cities and Provinces. After the motions of Kovacs were filmed by digital highspeed camcorder setting in 90 frames/s, kinematical data were calculated through DLT method. The variables were computed in the lapse time, the joint angle, the position·velocity of body COG, the inferred tension force of bar, and body COG path were simulated according to skill level of Kovacs. Results: Firstly, it was revealed that the lapse time was 1.19±0.03 s in the swing phase, and 0.83±0.03 s in the aerial phase. Secondly, it was revealed that the shoulder·hip joint motions of S1 and S2 were better than the other subjects in the swing phase, and the knee joint motions of S1 and S2 were better than the other subjects in the aerial phase. Thirdly, it was revealed that the horizontal·vertical velocity of body COG were -1.40±0.03 m/s, 3.80±0.07 m/s respectively, and the vertical positions of S1 and S2 were higher a little than the other subjects. Lastly, the skill level of Kovacs of this subjects was evaluated into 3 steps; excellent, advanced, normal. They need to train the swing motion including a giant circle, and body motions in the air. Conclusion: It would be suggested that Korean domestic players should improve to increase the vertical velocity at release instant and train to control the limbs elaborately in the air.